Managed aquifer recharge: the solution for water shortages in the Fergana Valley - Karimov, Akmal A.; Smakhtin, Vladimir U.; Mavlonov, A.; Borisov, V.; Gracheva, I.; Miryusupov, F.; Djumanov, J.; Khamzina, T.; Ibragimov, R.; Abdurahmanov, Botir (International Water Management Institute, 2013)
Doubling of population, since the 1970s, in the Aral Sea Basin of Central Asia led to the increased demand for water and energy. The shift of the key upstream reservoir on the Naryn River, main tributary of the Syrdarya River, from irrigation to hydropower generation reduced available water for irrigation in the summer and created excessive flows in the winter. The downstream reservoirs do not have free capacities for storing the excessive winter flows. This report examines the possibility of additional subsurface storages of water in a part of the Syrdarya River Basin, the Fergana Valley. The report aims to bring the attention of policymakers to alternative development of basin water management, which requires cooperation of riparian states in the use of water and energy.